Might Routine Vitamin A Monitoring in Cystic Fibrosis Patients Reduce Virus-Mediated Lung Pathology? - Sealy, Robert E.; Surman, Sherri L.; Vogel, Peter; Hurwitz, Julia L. (Frontiers in Immunology, 2021)
Cystic fibrosis (CF) is an autosomal recessive gene disorder that affects tens of thousands of patients worldwide. Individuals with CF often succumb to progressive lung disease and respiratory failure following recurrent infections with bacteria. Viral infections can also damage the lungs and heighten the CF patient’s susceptibility to bacterial infections and long-term sequelae. Vitamin A is a key nutrient important for immune health and epithelial cell integrity, but there is currently no consensus as to whether vitamin A should be monitored in CF patients. Here we evaluate previous literature and present results from a CF mouse model, showing that oral vitamin A supplements significantly reduce lung lesions that would otherwise persist for 5-6 weeks post-virus exposure. Based on these results, we encourage continued research and suggest that programs for the routine monitoring and regulation of vitamin A levels may help reduce virus-induced lung pathology in CF patients.